Chapter Le molestie sessuali online tra adolescenti: che cosa sono e come si manifestano - Franceschi, Angela (Studies on Adult Learning and Education, 2022)
Sexual harassment is a complex behaviour, characterized by several dimensions and definitions, as shown by the literature. In an online context, it is important to fully understand its nature, characteristics and consequences as well as how it may affect adolescents. This work aims to systematize the information available in the literature, by describing the main characteristics of the phenomenon, and trying to provide a definition. The research, which was conducted on four databases in November 2021, led to the identification of 20958 works. After removing the duplicates, and analyzing the abstracts and full-texts, a final number of 65 works were included, which were read in full-text and analysed. As for the studies collected, the type of relationship between the aggressor and the victim is described, alongside a description of the behaviors classified as online sexual harassment. Online sexual harassment can manifest itself in three main typologies (verbal, visual, cybersexual). Within these typologies, it is possible to identify three prevalent behaviours: unwanted solicitation, non-consensual sexting, and sharing of intimate and/or private content with third parties without the victim's consent.